Physiological predictors of performance in cross-country skiing from treadmill tests in male and female subjects - Larsson, P.; Olofsson, P.; Jakobsson, E.; Burlin, L.; Henriksson-Larsen, K. (Scandinavian Journal of Medicine & Science in Sports, 2002)
In order to study which parameter that best corresponds to performance during cross-country skiing, seven male and nine female cross-country skiers were tested with treadmill tests. Parameters measured or computed by metabolic gas measurements were the anaerobic threshold (AT), threshold of decompensated metabolic acidosis (TDMA), the exercise intensity where the Respiratory exchange ratio reaches 1.0 (R = 1) and peak oxygen (O2) uptake (VO2peak). Onset of blood lactate accumulation (OBLA, 4 mmol.l-1 blood lactate) was also measured. The various parameters were measured in percentage of maximal heart rate, percentage of peak O2 uptake, VO2 ml.kg-1.min-1, VO2 ml.min-1.kg-2/3 and VO2 l.min-1. Results from four large competitions were also collected to rank the subjects. With correlation analysis, it was revealed that in male subjects a high OBLA was associated with good ranking results (r = (-0.829) - (-0.964); P < 0.05-0.001). In female subjects, the best association with competition results was found for R = 1 (r = (-0.715) - (-0.810); P < 0.05). Concerning VO2 measurements, for male subjects the unit l.min-1 is suggested to be used and for female subjects either the units l.min-1, ml.min-1.kg-2/3, or ml.kg-1.min-1 could be used when predicting performance in cross-country skiing. In conclusion, treadmill tests can be used for the prediction of performance in cross-country skiing. Further, various parameters from treadmill tests in men and women are best used as predictors of performance in cross-country skiing.